Red blood cell indices versus serum ferritin as surrogate markers of iron deficiency during pregnancy - Ochuwa Adiketu Babah; Chisom Florence Chieme; Ajibola Ibraheem Abioye; Samuel Olusegun Spaine; Titilope Adenike Adeyemo; Bosede Bukola Afolabi (PLoS ONE, 2025)
Background Serum ferritin testing is the most commonly used method for screening for iron deficiency. However, iron deficiency screening is not routinely done in low-middle-income countries, including Nigeria, often due to the cost of laboratory evaluation. Aim This study determined the diagnostic value of red blood cell indices, which are cheaper and quicker to conduct, compared to serum ferritin to diagnose iron deficiency during pregnancy. Methodology A cross-sectional study of 857 pregnant women at 36 weeks gestation in Nigeria. Standard laboratory techniques assayed mean corpuscular volume (MCV), mean cell haemoglobin (MCH), mean cell haemoglobin concentration (MCHC), red cell distribution width (RDW) and serum ferritin. Spearman’s rank correlation coefficient of each of the complete blood count parameters (MCV, MCH, MCHC and RDW) with serum ferritin were assessed and their diagnostic accuracy relative to iron deficiency (defined as ferritin <30ng/mL) was evaluated. Results Mean age of the pregnant women was 27.7 ± 5.8 years. Median (IQR) was 10.3 (IQR: 9.6–11.0) g/dL for haemoglobin, and 84.0 (IQR: 47.0–157.9) ng/mL for ferritin. Serum ferritin levels have significant correlation with RDW, r = −0.12, p < 0.001 and MCH, r = 0.10, p = 0.003; but not with MCV, r = 0.06, p = 0.083 and MCHC, r = 0.04, p = 0.293. RDW was found to be the best discriminator for iron deficiency based on area under curve (AUC) 59.9% (95%CI: 56.6% – 63.2%), sensitivity 65.6% and specificity 53.8% at best cut-off 14.7fL. On restricting analysis to those with anaemia, the findings did not change materially. Conclusion The diagnostic value of red blood cell indices, compared to serum ferritin, in detecting iron deficiency and iron deficiency anaemia is poor and should not play a role in diagnosing iron deficiency in pregnancy in a low-resource setting.